Prediction Method of Sealing Capacity Distribution of Regional Mudstone Caprocks Damaged by Fault During the Hydrocarbon Accumulation Period - Han, Xu; Fu, Guang; Liang, Mugui; Jin, Fengming; Han, Guomeng; Jiang, Wenya (Frontiers in Earth Science, 2022)
In order to study the distribution law of oil and gas above and below the regional mudstone caprocks damaged by fault in petroliferous basins, based on the study of the sealing mechanism and degree of regional mudstone caprocks damaged by fault during the hydrocarbon accumulation period, the paleo-juxtaposition thickness of regional mudstone caprock was calculated by determining the paleo-fault throw of faults and the paleo-thickness of regional mudstone caprocks during the hydrocarbon accumulation period. According to the relation between the paleo-juxtaposition thickness of regional mudstone caprocks at known well points in the study area and the distribution of oil and gas above and below the regional mudstone caprock, the maximum juxtaposition thickness required for the upper and lower connection of the fault-associated fracture zone in the regional mudstone caprock was determined. On this basis, a set of prediction methods for the sealing capacity of regional mudstone caprocks damaged by fault during the hydrocarbon accumulation period was established. Then, this method was applied to the prediction of the damage degree distribution of the Zhangdong Fault to the regional mudstone caprock of the middle sub-member of the first member of the Shahejie Formation in the middle and late depositional periods of the Minghuazhen Formations in Qikou Sag of the Bohai Bay Basin during the hydrocarbon accumulation period. The results show that the damage degree of the Zhangdong Fault to the regional mudstone caprock of the middle sub-member of the first member of the Shahejie Formation during the hydrocarbon accumulation period is large. The largest damage appears in the east, with an a-value greater than 1, followed by the west, with an a-value between 0.5 and 1. The relatively minor damage occurs in the middle west part, with an a-value less than 0.5. The middle part is conducive to the accumulation and preservation of oil and gas generated from the source rock of the underlying third member of the Shahejie Formation, which is consistent with the fact that oil and gas discovered in the lower sub-member of the first member of the Shahejie Formation near the Zhangdong Fault are mainly distributed in its middle part. It shows that this method is feasible to predict the damage degree distribution of regional mudstone caprocks during the hydrocarbon accumulation period.